Rapid production of multimeric RNA aptamers stabilized by a designed pseudo‐circular structure in E. coli. Issue 3 (5th December 2022) - Zou, Zongsheng; Younas, Tayyaba; Dumsday, Geoff; Haritos, Victoria S.; He, Lizhong
Abstract: RNA aptamers bind specifically and selectively to various macromolecules, cell surfaces, and viruses and find broad applications as biosensors, diagnostics, and in therapeutic treatments and drug delivery. Currently, RNA aptamer production is via in vitro methods. Herein, a new E. coli ‐based approach has been demonstrated for the rapid production of multimeric RNA aptamer transcripts that are protected from degradation by burying the 5′ and 3′ ends of the transcript in a designed double‐stranded spacer. Multimeric and fluorescent RNA aptamers were produced stably in vivo and readily isolated from RNase III‐deficient cells, and their full functionalities were shown by binding assays and fluorescence measurements. This approach shows promise as a rapid and scalable bioprocess for the production of RNA aptamers at low cost. Graphical Abstract and Lay Summary: RNA aptamers have broad application ranging from biosensors and diagnostics to therapeutic treatments and drug delivery. In this study, the authors describe the design and testing of pseudo‐circular RNAs which are resistant to degradation by E. coli exoribonucleases. RNA aptamers produced in vivo are protected by burying the 5′ and 3′ ends of the transcript in a designed double stranded spacer. The method reported here offers a rapid and scalable bioprocess for production of RNA aptamers at low cost.